Constraints on space-time manifold in Euclidean supergravity in terms of Dirac eigenvalues - Ciuhu, C.; Vancea, Ion V. [UNESP] (World Scientific Publishing, 2000)
We generalize a previous work on Dirac eigenvalues as dynamical variables of Euclidean supergravity. The most general set of constraints on the curvatures of the tangent bundle and on the spinor bundle of the space-time manifold, under which space-time admits Dirac eigenvalues as observables, are derived.
Keywords: acceleration; atomic particle; calculation; geometry; gravity; mathematical analysis; mathematics; quantum theory